Histopathology of marine and freshwater fish lymphocystis disease virus (LCDV) - Mosharrof Hossain; Myung-Joo Oh (Universiti Kebangsaan Malaysia, 2011)
Lymphocystis disease (LCD) in fishes is caused by the agent called lymphocystis disease virus (LCDV). LCDV is a chronic and benign virus. The disease affects 96 species of marine and fresh water fishes ranged among 34 families in the world. Affected fish with LCD has a typical external symptom with clusters consisted of enormously hypertrophied dermal cells on the skin and fins. The hypertrophied cells, generally named lymphocystis cells, have a thick hyaline capsule, an enlarged nucleus and prominent basophilic cytoplasmic inclusions. Among the four species of fishes, olive flounder Paralichthys olivaceus, and rockfish Sebastes schlegeli were marine cultured fish, and gourami Trichogaster leeri and painted glassfish Channa baculis were freshwater ornamental fish. Although LCD causes low mortality, the disfigurement of infected fish can make them unsellable. Thus LCD has resulted in an important economic loss in the aquaculture industry. This study of histopathology may be adequate for a presumptive diagnosis of lymphocystis diseases both in marine and freshwater fish species.